2016
DOI: 10.14260/jemds/2016/290
|View full text |Cite
|
Sign up to set email alerts
|

A Correlative Study on Serum Lipid Profile and Osteogenic Mineral Status in Osteoporosis

Abstract: BACKGROUNDOsteoporosis is a condition where the structural and functional integrity of the bones are altered to an extent where the bone material is not sufficiently completed enough to perform its basic function of support, load bearing and component of metabolic pool of osteogenic minerals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The positive relationships of TC and TG levels with osteoporosis in our study are consistent with some previous studies [19,23,25,29]. Lahon et al [20] and Ersoy et al [18] reported a negative correlation between TC and TG levels and osteoporosis. In addition, Ghadiri-Anari et al [21], Cui et al [22], Li et al [24] and Jeong et al [30] found that there was no association between lipid pro les and osteoporosis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The positive relationships of TC and TG levels with osteoporosis in our study are consistent with some previous studies [19,23,25,29]. Lahon et al [20] and Ersoy et al [18] reported a negative correlation between TC and TG levels and osteoporosis. In addition, Ghadiri-Anari et al [21], Cui et al [22], Li et al [24] and Jeong et al [30] found that there was no association between lipid pro les and osteoporosis.…”
Section: Discussionsupporting
confidence: 93%
“…Lipid pro le is useful for assessing risk of CVDs [14]. There is also vitro evidence suggesting lipids are involved in the development of osteoporosis [15].However, the association between lipid pro le and osteoporosis in human studies is still controversial [16][17][18][19][20][21][22][23][24][25]. Majority of human studies suggested there were negative associations between lipid biomarkers and bone mineral density (BMD) [16,17,19,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are also in line with the findings reported by Ghadiri-Anari A et al [ 21 ], those found insignificant associations between lipids and BMD. However, existing epidemiological studies suggested that there are still conflicting associations of HDL-C and LDL-C with osteoporosis [ 17 , 18 , 20 ]. These conflicting results are likely attributed to the different study sample sizes, study populations and covariates adjusted in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of human studies suggested that there were negative associations between lipid biomarkers and bone mineral density (BMD) [ 16 , 17 , 19 , 22 25 ]. However, Ersoy et al [ 18 ] and Lahon et al [ 20 ] found that low-density lipoprotein cholesterol (LDL-C) was positively correlated with BMD. Ghadiri-Anari et al [ 21 ] suggested a null association between lipids and BMD.…”
Section: Introductionmentioning
confidence: 99%